find g(6+h), g(6), g(6+h)-g(6)

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

g(x)=x^2+8x+7 

May 5th, 2015

g (6) = 6^2 +48 +7 =91

g (6+h) = (6+h)^2+8 (6+h) +7  = 36 +h^2+12h+48+8h+7 = h^2+20h+91

g (6+h) - g (6) = h^2+20h+91 -91

                         = h^2+20h

Please let me know if you have any questions and best me if you are satisfactory.


May 5th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 5th, 2015
...
May 5th, 2015
Sep 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer